KAJIAN STRUKTUR KEPRIBADIAN PADA TOKOH UTAMA DALAM NOVEL SI ANAK PEMBERANI KARYA TERE LIYE - Firda Oktaviani; Alfi Nur Khasanah; Cintya Nurika Irma (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
Si Anak Pemberani novel by Tere Liye can be used as reference in understanding the world of children, particularly on personality. Their personalities s that are presented by child make this topic interesting to be studied. This research is a descriptive narrative research. The data in this research are in the form of excerpts from the novel Si Anak Pemberani by Tere Liye which contains aspects of literary psychology.The data was collected used library techniques, reading techniques and note taking techniques. The data validity techniques used in this study are source triangulation, data tiltulation, and method triangulation. The Purpose of the research to explain the psychological aspects of the personality of the main character in Si Anak Pemberani novel. The conclusion of this study are the character Eliana has a personality aspect that is the structure of dynamism includes courage, assertiveness, and high curiosity, aspects of personification and aspects of cognitive processes include, prototype, parataxic, and syntactic ways of thinking. Keywords : personality psychology, Si Anak Pemberani novel